Representasi Guru sebagai Agen Perubahan: Analisis Semiotika Motivasi Belajar dalam Film Radical (2023) - Ronald Del Piero Ronald (Universitas Pancasakti Tegal, 2025)
The movie Radical (2023) is one of the movies with the theme of education, showing the struggle of a teacher in facing great challenges in teaching his students. This study aims to identify and interpret visual and narrative elements related to learning motivation.The research method used in this journal adopts a qualitative approach using semiotic analysis.The results show that based on the inspirational character of the teacher, the interaction between teachers and students and the context of the educational environment built, Radical successfully presents a picture of how a teacher can be an influential agent of change in the lives of his students, both in terms of academics and their personal development.The conclusion of this study shows that the character of the teacher in the film is portrayed as an inspirational figure, able to have a positive impact on changes in students. The interaction between teachers and students, shown in the movie, depicts a caring, understanding, and motivational relationship, where teachers act as mentors who encourage students to explore their potential.